Managing systems maintenance - Perry, William E. (Wellesley, MA. : Q.E.D. Information Sciences, 1981)
The book is aimed at incorporating good system maintenance practice, while eliminating ineffective practices.
Includes indexes.
ijb 16/01/2019
Loans
Keywords: Software maintenance